Determinants of Stunting and Child Development in Jombang District - Rahmawati, Vivin Eka; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Stunting is a very short body state in children that goes beyond the 2 SD deficit below the child population height. Worldwide stunting affects about 162 million children under five. Indonesia is included in 17 countries that have three nutritional problems in children under five: stunting, wasting, and overweight. This study aimed to investigate the determinants of stunting and child development in children under five.Subjects and Method: This was a retrospective cohort study conducted at Mayangan and Jarak Kulon Community Health Centers, Jombang, East Java, in Januari 2018. A total sample of 58 children were selected for this study by fixed exposure sampling. The dependent variables were stunting and child development. The independent variables were birth-length, maternal age, maternal height, maternal education, and family income. The data were collected by questionnaire. Data on birth length was taken from maternal and child record at community health center. The data were analyzed by path analysis model.Results: The likelihood of good child development increased with maternal education (b= 1.08; 95% CI= 0.41 to 1.75; p= 0.001) and decreased with stunting (b= -0.78; 95% CI= -1.46 to -0.10; p=0.025). The risk of stunting decreased with birth-length (b= -0.90; 95% CI= -1.60 to -0.21; p=0.011) and maternal height (b=-0.92; 95% CI= -1.69 to -0.16; p=0.018). The risk of stunting increased with maternal age <20 y.0. or ≥35 y.o. at pregnancy (b= 0.73; 95% CI= -0.03 to 1.46; p=0.051). The likelihood of maternal age <20 y.0. or ≥35 y.o. at pregnancy decreased with higher education (b=-0.75; 95% CI= -1.44 to -0.06; p=0.033). Birth-length  increased with maternal height (b= 1.07; 95% CI= 0.28 to 1.86; p= 0.008) and higher family income (b=0.93; 95% CI = 0.29 to 1.57; p=0.004). Birth-length decreased with maternal age <20 y.0. or ≥35 y.o. at pregnancy (b=-0.74; 95% CI= -1.48 to -0.01; p=0.047).Conclusion: The likelihood of good child development increases with maternal education and decreases with stunting. The risk of stunting decreases with birth-length and maternal height, and increases with maternal age <20 y.0. or ≥35 y.o. at pregnancy.Keywords: child development, stunting, birth-length, maternal age at pregnancy, maternal education, and family incomeCorrespondence: Vivin Eka Rahmawati. Masters Program in Public Health, Univesitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: vivineka74@gmail.com.Journal of Maternal and Child Health (2018), 3(1): 68-80https://doi.org/10.26911/thejmch.2018.03.01.07